Penyampaian Informasi Kebudayaan Indonesia di Akun Instagram @kemenparekraf.ri - Kholifah, Setya; Paramita, Sinta; Irena, Lydia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This research aims to analyse the public communication conducted by the Ministry of Tourism and Creative Economy (Kemenparekraf) through the Instagram account @kemenparekraf.ri in conveying Indonesian cultural information to the public. Using a descriptive qualitative approach and case study method, this research identifies how the ministry utilises Instagram in public communication to promote Indonesian culture. The researcher analysed the four pillars of public communication applied in the Instagram account, namely informative, educative, entertainment, and interactive content. The results showed that the Instagram account @kemenparekraf.ri succeeded in attracting audience attention with relevant, interesting, and easy-to-understand content. Professional content and visual quality as well as simple language make Indonesian cultural information well received. Evaluation through social media metrics shows high audience interaction with the content presented. However, some content needs to be strengthened in its narrative to increase the impact of cultural messages. This research provides insights for public communication strategies in cultural promotion through social media. Penelitian ini bertujuan menganalisis komunikasi publik yang dilakukan oleh Kementerian Pariwisata dan Ekonomi Kreatif (Kemenparekraf) melalui akun Instagram @kemenparekraf.ri dalam menyampaikan informasi kebudayaan Indonesia kepada masyarakat. Dengan menggunakan pendekatan kualitatif deskriptif dan metode studi kasus, penelitian ini mengidentifikasi bagaimana Kemenparekraf memanfaatkan Instagram dalam komunikasi publik untuk mempromosikan kebudayaan Indonesia. Peneliti menganalisis empat pilar komunikasi publik yang diterapkan dalam akun Instagram tersebut, yaitu konten informatif, edukatif, hiburan, dan interaktif. Hasil penelitian menunjukkan bahwa akun Instagram @kemenparekraf.ri berhasil menarik perhatian audiens dengan konten yang relevan, menarik, dan mudah dipahami. Isi konten dan kualitas visual yang profesional serta bahasa yang sederhana membuat informasi kebudayaan Indonesia diterima dengan baik. Evaluasi melalui metrik media sosial menunjukkan tingginya interaksi audiens dengan konten yang disajikan. Namun, beberapa konten perlu diperkuat narasinya untuk meningkatkan dampak pesan kebudayaan. Penelitian ini memberikan wawasan untuk strategi komunikasi publik dalam promosi kebudayaan melalui media sosial.